PERALIHAN HAK ATAS TANAH YANG DILAKUKAN OLEH MASYARAKAT ADAT SIMALUNGUN DI KECAMATAN PANOMBEAN PANEI KABUPATEN SIMALUNGUN - YOLANDA REGINA PURBA (PREMISE LAW JURNAL, 2017)
The legality of land title transfer owned by the adat community whose land is uncertified and the transfer is transparently witnessed by an adat leader and the other witnesses from both parties is valid, as far as both parties do their task in paying off and transferring the land. In general, uncertified adat land is transferred transparently, in cash, and witnessed by an adat leader and witnesses from both parties; this especially occurs in Panombean Panei Subdistrict, Simalungun Regency. The inhibiting factors in the implementation of land title transfer owned by an individual legally are as follows: lack of clarity of the parties concerned in explaining the adat land status, lack of clarity in its borders, and disapproval of family members and adat leader. This lack of clarity is caused by the difficulty in fulfilling the requirements for transferring an adat land in Panombean Panei Subdistrict, Simalungun Regency.Keywords: Communal Land, Customary Law Society, Simalungun.